Phaseless planar near‐field antenna measurements: some aspects of aperture's mask and alignment error. Issue 17 (1st August 2015) - Shakhtour, H.; Heberling, D.
Abstract : A quick review of the planar phaseless near‐field antenna measurement technique is presented and some interesting aspects related to the size of the mask used at the aperture of the antenna under test (AUT) are pointed out. It is shown simulatively and experimentally that due to the edge fields the AUT aperture's mask needs to be larger than the physical aperture of the AUT to achieve better accuracy. In addition, the misalignment of the setup has a big impact on the achieved far‐field accuracy. This is emphasised experimentally.